A STRATEGIC, PROCESS-ORIENTED APPROACH FOR AN ESP READING COURSE IN THE HUMANITIES - Placci, Graciela; Longhini, Ana María (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper aims at describing pedagogical materials especially designed for an ESP (English for Specific Purposes) course for undergraduate students in the Humanities and Social Sciences (mainly majoring in Education, History, and Geography) at a national public university in Argentina. It expands on the rationale behind the methodology and its practical application. The lessons in the manual seek to transfer to practical application theories based on the latest findings in reading, cognitive psychology and educational psychology. The contribution of the learner's systemic knowledge, exploited in cross-reference with their schematic knowledge, plus the application of metacognitive and monitoring strategies have been our guidelines for the design of the activities. Since our main aim is to facilitate the learners’ interpretation of texts while simultaneously improving their language skills, we base our approach on systemic functional grammar. Each lesson we teach addresses questions aimed at unveiling the ideational, interpersonal, and textual meanings of the reading texts that we use as didactic units.